Consulta de enfermagem na estratégia saúde família com pessoas que têm diabetes mellitus: construção participativa - Silva, Silvana de Oliveira (2023)
He nursing consultation (NC) stands out as crucial in the care of individuals with Diabetes Mellitus (DM), as it is a disease with a strong social impact responsible for the leading causes of death worldwide. Brazil holds the first position in Latin America in the number of people with DM. This scenario requires strengthening and qualifying actions based on a user-centered health care model that presupposes comprehensive, proactive, longitudinal, and resolutive care. This study aimed to analyze the constitutive elements that underpin nursing consultation with people with DM in the Family Health Strategy and to develop an educational process based on the assumptions of the Chronic Care Model (CCM) and mediated by a reflective-dialogical process with nurses, aiming at improving NC with individuals with DM. This is a qualitative, convergent-care research conducted in Family Health Strategies (FHS) in a municipality in the central-west region of RS. The participants in the study are nurses affiliated with FHS and the primary care nursing manager with experience in NC with individuals with DM. The approach to the field began in August 2020, and data were collected from October 2020 to December 2021 through participant observation, semi-structured interviews, and convergence groups. The analysis process was participatory, involving the production of narratives with an interpretative approach. The study was reviewed and approved by the Research Ethics Committee (CEP) of UFSM, under the number CAAE 36038620.8.0000.5346. The results revealed that nurses aim to promote self-care, establish a connection with users, and support lifestyle changes in individuals with DM through NC, and these elements are aligned with the CCM. Among the elements that deviate from the CCM, attitudes, values, and knowledge were identified that weaken nursing care during NC, including reactive, prescriptive, verticalized, and analogous approaches for all users. Gaps in theoretical and practical knowledge, challenges, and potentialities of the context Hn which NC is developed were identified. Points of convergence were established to improve the quality of NC with individuals with DM, including deepening theoretical and practical knowledge of the CCM and NC in DM, addressing workload overload, and implementing a guide for NC. Impacts were observed, such as strengthening the autonomy of nurses through reliable sources of knowledge, fostering critical thinking through reflection on reality, a conscious pursuit of improvement, transformation of practice, and redefinition of the user-centered relationship generated in the NC process. It is concluded that NC was enhanced through the active participation of nurses in the educational-reflective-dialogical process, as they positioned themselves to intervene in this reality and achieve an improvement in the quality of NC they provide. Mixed and quantitative studies with nurses are suggested to establish relationships and measure the impact of CCM-based NC on the health of individuals with DM.